A DETAILED ANALYSIS OF THE DEGREES OF BURNOUT AND TEACHER STRESS-MANAGEMENT TECHNIQUES IN UNIVERSITY LECTURERS - Guerrero Barona, Eloísa (Anales de Psicología / Annals of Psychology, 2003)
In this study the different degrees of burnout and stress-management techniques are compared. The aim is to see if there is a relation between the levels of burnout and the different stress-management techniques which are adopted by teachers. Maslach’s Inventory (Maslach and Jackson, 1986) or M.B.I. and the evaluation scale of stressmanagement or C.O.P.E. (Carver, Scheier and Weintraub, 1989) were used in the study. Certain results show that teachers who suffer from a high degree of emotional exhaustion use techniques involving emotional unburdening, behavioural disconnection, drug-taking and acceptance of the situation (passive techniques) On the other hand, those teachers who show a high degree of personal attainment use techniques involving active confrontation, planning, seeking instrumental and social help, having a positive view of the situation and decreasing confrontational situations (active techniques)